Al-Taʻrīb - Institut Agama Islam Negeri Palangka Raya. Program Studi Pendidikan Bahasa Arab (Arabic Education Department PBA, the Faculty of Education and Teacher Training (FTIK), State Islamic Institut (IAIN) of Palangka Raka, 2013)
Original research articles, review articles, and short communications, including 1) Teaching Arabic as a Foreign Language, 2) Arabic Linguistic, 3) Arabic Literature, 4) History of Arabic Education, 5) Strategy of Arabic Teaching, 6) Media of Arabic Teaching, 7) Technology of Arabic Teaching, 8) Modern Standard Arabic, 9) Arabic Second Language Acquisition.
Keywords: Arabic language : Periodicals; Arabic language : Study and teaching : Periodicals; Arabic language : Study and teaching; Arabic language